El «Nou Diccionari Normatiu de la Llengua Catalana» - Cabré, M. Teresa; Bozzo, Maria; Egea, Àngels; Juncadella, Marta; Santamaria, Carolina (Caplletra. Revista Internacional de Filologia, 2015)
This article describes the process by which the Nou Diccionari Normatiu de la Llengua Catalana (NDNLC) has been made; this dictionary brings up to date and regularizes Pompeu Fabra’s Diccionari General de la Llengua Catalana (DGLC), which implies, on the one hand, adding to the dictionary new words brought about by different social habits and by the progress of Science and technology, and, on the other hand, bringing the contents of the dictionary up to date. This project has been carried out in three different phases. The first consisted in creating a general Computer data base (BDOL) which contains, besides the DGLC, words belonging both to the common language and to specific fields; in this first phase a study of the DGLC was also carried out, with two aims: a) to analyse the text itself and in doing so select whatever Information might be considered obsolete today, and b) to find out the criteria which Fabra used to make the dictionary, which are implicit in the text. In the second phase the lexicographic criteria by which the dictionary was to be made were established, its entries (both words and phrases) were selected, the old articles were revised and new ones were created. Finally, in the third phase the data base specifically for the NDNLC was created; this contains all the Information of the Nou Diccionari Normatiu de la Llengua Catalana, organised into articles.